Reproductive phasiRNA loci and DICER-LIKE5, but not microRNA loci, diversified in monocotyledonous plants. Issue 4 (13th January 2021) - Patel, Parth; Mathioni, Sandra M; Hammond, Reza; Harkess, Alex E; Kakrana, Atul; Arikit, Siwaret; Dusia, Ayush; Meyers, Blake C
Abstract: In monocots other than maize ( Zea mays ) and rice ( Oryza sativa ), the repertoire and diversity of microRNAs (miRNAs) and the populations of phased, secondary, small interfering RNAs (phasiRNAs) are poorly characterized. To remedy this, we sequenced small RNAs (sRNA) from vegetative and dissected inflorescence tissue in 28 phylogenetically diverse monocots and from several early-diverging angiosperm lineages, as well as publicly available data from 10 additional monocot species. We annotated miRNAs, small interfering RNAs (siRNAs) and phasiRNAs across the monocot phylogeny, identifying miRNAs apparently lost or gained in the grasses relative to other monocot families, as well as a number of transfer RNA fragments misannotated as miRNAs. Using our miRNA database cleaned of these misannotations, we identified conservation at the 8th, 9th, 19th, and 3′-end positions that we hypothesize are signatures of selection for processing, targeting, or Argonaute sorting. We show that 21-nucleotide (nt) reproductive phasiRNAs are far more numerous in grass genomes than other monocots. Based on sequenced monocot genomes and transcriptomes, DICER-LIKE5, important to 24-nt phasiRNA biogenesis, likely originated via gene duplication before the diversification of the grasses. This curated database of phylogenetically diverse monocot miRNAs, siRNAs, and phasiRNAs represents a large collection of data that should facilitate continued exploration of sRNA diversification in flowering plants. Abstract : Among monocots, loci generating 21-nt reproductive phased, secondary, small interfering RNAs amplified and diversified in grass genomes while microRNA-producing loci did not.